Economic Feasibility of Tourism-Based MSMEs: A Cost-Benefit Analysis from Carita Beach, Indonesia - Aep Saefullah; Moh Tahang; Ith Vuthy (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2026)
Tourism-based Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in supporting local economies in coastal destinations such as Carita Beach, Indonesia. Despite their economic potential, these enterprises face significant uncertainty due to fluctuating tourist arrivals and seasonal demand patterns. The originality of this study lies in applying a simplified Cost-Benefit Analysis (CBA) framework tailored to small-scale, tourism-based MSMEs using empirical field data. This study aims to analyze the cost and benefit structure and evaluate the economic feasibility of MSME development in the tourism sector. The research was conducted on February 15–17, 2026, using an economic managerial approach, with data collected through observations and in-depth interviews involving 50 MSME actors across culinary, rental, and tourism service sectors. The empirical results reveal that all business categories demonstrate a Benefit-Cost Ratio (BCR) greater than 1, indicating economic feasibility. Specifically, rental MSMEs show the highest BCR (1.48), followed by tourism services (1.45) and culinary MSMEs (1.23). However, variations in cost structures and dependency on tourist flows influence the level of profitability and resilience. The findings imply that strengthening cost efficiency, improving basic financial recording practices, and adopting adaptive business strategies are essential to enhance the sustainability of MSMEs in tourism-dependent areas.